2006
DOI: 10.3406/arch.2006.4028
|View full text |Cite
|
Sign up to set email alerts
|

The Art of the Qur'an in Banten: Calligraphy and Illumination

Abstract: Annabel Teh Gallop, The British Library, London & Ali Akbar, Office for Research, Development and Training, Ministry of Religious Affairs, Jakarta The Art of the Qur'an in Banten: Calligraphy and Illumination Cet article traite de treize copies du Coran de Banten, datant pour la plupart du XVIIIe s. et qui, par bien des aspects, diffèrent de celles des autres pays d'Asie du Sud-Est. Dans ce corpus, deux groupes peuvent être identifiés : l'un constitué par de très grandes copies destinées à des instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Again we look to any potential borrowings from illuminated manuscripts. A comprehensive art historical study through visual analysis of Islamic manuscripts from Banten, found the manuscripts to be unusual in the Malaya world in that they were mostly not illuminated [48,49]. The three that were illuminated were also unusual in their colour scheme.…”
Section: Discussionmentioning
confidence: 99%
“…Again we look to any potential borrowings from illuminated manuscripts. A comprehensive art historical study through visual analysis of Islamic manuscripts from Banten, found the manuscripts to be unusual in the Malaya world in that they were mostly not illuminated [48,49]. The three that were illuminated were also unusual in their colour scheme.…”
Section: Discussionmentioning
confidence: 99%
“…Now three manuscripts are stored at National Library (A 51; A 54; W. 277) and the rest was stored at Masjid Agung Banten. (Gallop and Akbar 2006); (Nurtawwab 2009: 49-51). According to Ekadjati and Darsa, there are 245 manuscripts of Islam, including thirteen qur'anic manuscripts and six qur'anic translations and commentaries, which stored at museums in West Java.…”
Section: The Firstmentioning
confidence: 99%